Pengaruh Free Cash Flow, Investment Opportunity Set (IOS), dan Financial Leverage terhadap Manajemen Laba - Savina Swari Arizoni; Andri Andri (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The purpose of this study is to determine the extent to which the investment opportunity set, financial leverage and free cash flow influence earnings management in manufacturing companies listed on the Indonesia Stock Exchange, observation period 2022-2023. Earnings management as the dependent variable is measured using discretionary accruals. Sampling in this study used a non-probability sampling technique (purposive sampling method) and based on the established criteria, only 129 companies were eligible to be sampled. Hypothesis testing in this study used multiple linear regression analysis. After being tested using SPSS version 25, the results of the study showed that the three independent variables, namely partially gave the result that only the second hypothesis was accepted, namely the investment opportunity set had a significant effect on discretionary accruals and simultaneously had a significant effect on earnings management.